Correlating p16INK4a /Ki-67 co-expression and gene methylation with HIV infection and high-risk HPV in abnormal cervical squamous intraepithelial cells - Louw, Meagan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.